PENGARUH ONLINE REKRUTMEN DAN REPUTASI PERUSAHAAN TERHADAP MINAT MELAMAR PEKERJAAN PADA GENERASI Z PENGGUNA PLATFORM TIKTOK DI PT. ES TEH INDONESIA - Chaeriyah, Hafidhatul; Kristian Halomoan2, Yan (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of online recruitment and company reputation on interest in applying for jobs among Gen Z users of the TikTok platform at PT. Indonesian Iced Tea Research was conducted among Generation Z users of the TikTok platform, with a population consisting of individuals born between 1995-2010, with a total of 96 respondents. The sampling technique used was purposive sampling, while data collection was carried out by distributing questionnaires online to 96 respondents. This study uses a quantitative approach. The collected data was analyzed using SPSS 26 software. Data analysis used validity tests, reliability tests, classical assumption tests, regression analysis, determination analysis and hypothesis testing. The research results show that company reputation has a significant and positive impact on interest in applying for jobs, while online recruitment also has a positive and significant influence on interest in applying for jobs. Based on the results of the analysis, the value of t calculated > t tally altalu (7.694 > 1.98552) means that H01 is rejected and Hal1 is accepted, this shows that there is a positive and significant influence on Online Recruitment Alntalral (X1) in relation to Employee Hiring (Y) . and the value of t calculated > t tallel altalu (6.165 >1.98552) means that H02 is rejected and Ha2 is accepted, this shows that there is a positive influence which is significant in terms of the overall reputation of the company (X2) on the employee turnover interest (Y). The value of Fcount > Ftable (40,549 > 3.09), this is also confirmed by the significance of 0.000 < 0.05. Thus, Ho3 is rejected and Ha3 is accepted, so it can be concluded that the variables Online Recruitment (X1) and Company Reputation (X2) have a joint (simultaneous) effect on Interest in Applying for a Job (Y).